Proposed Methods and Endpoints for Defining and Assessing Adverse Environmental Impact (AEI) on Fish Communities/Populations in Tennessee River Reservoirs - Gary D. Hickman; Mary L. Brown (The Scientific World Journal)
Two multimetric indices have been developed to help address fish community (reservoir fish assemblage index [RFAI]) and individual population quality (sport fishing index [SFI]) in Tennessee River reservoirs. The RFAI, with characteristics similar to the index of biotic integrity (IBI) used in stream fish community determinations, was developed to monitor the existing condition of resident fish communities[1,2,3]. The index, which incorporates standardized electrofishing of littoral areas and experimental gill netting for limnetic bottom-dwelling species, has been used to determine residential fish community response to various anthropogenic impacts in southeastern reservoirs.